Editorial - Soares, Adriana Benevides; Mendes, Deise Maria Fernandes; Valentim, Renata Patrícia Forain de; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2016)
Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Deise Maria Fernandes Mendes, Marcia Moraes, Renata Patrícia Forain de Valentim, Rita Maria Manso de Barros